# What is the solution of x^2 - 2x + 1 = 0

*print*Print*list*Cite

### 3 Answers

The equation x^2 - 2x + 1 = 0 has to be solved for x.

x^2 - 2x + 1 = 0

=> x^2 - x - x + 1 = 0

=> x(x - 1) - 1(x - 1) = 0

=> (x - 1)(x - 1) = 0

**This gives the roots of the equation {1, 1}**

x^2 - 2x + 1 = 0

=> (x - 1)^2 = 0

=> x = 1

The answere is 1

Using Completeing the Square

x^2-2x+1=0

x^2-2x=-1

x^2-2x+(2/2)^2=-1+(2/2)^2

x^2-2x+1^2=-1+1

Using the identity **a^2-2ab+b^2=(a-b)^2**

(x-1)^2=0

`sqrt(x-1^2)` =`sqrt(0)`

x-1=0

x=1